Impact of soil tillage on the robustness of the genetic component of variation in phosphorus (P) use efficiency in barley (Hordeum vulgare L.) - George, Timothy S; Brown, Lawrie K; Newton, Adrian C; Hallett, Paul D; Sun, Ben Hua; Thomas, William T. B; White, Philip J (Plant and soil, 2011)
To enhance the sustainability of agriculture it is imperative that the use of P-fertilisers by temperate cereal crops be improved. This can be achieved both by agronomic and genetic approaches. While many studies have demonstrated genotypic variation in P-use efficiency in a number of cereal species the robustness of this genetic variation in contrasting environments is rarely considered. In this paper we describe an experiment in which we compare the P-nutrition of winter and spring barley genotypes from an association genetic-mapping population grown in a field trial with different cultivation treatments (conventional plough vs. minimum tillage) which had been established over a number of years. We demonstrate that, while there is significant variation between genotypes in their P nutrition, this variation is not comparable between cultivation treatments and only one winter barley genotype (cv. Gleam) has beneficial P-use efficiency traits in both cultivation systems. Analysis of the association genetic-mapping population demonstrated that there was a strong environmental component in the genotypic variation, with more significant associations of shoot P concentration with known SNP (Single Nucleotide Polymorphism) markers when the population was grown in minimum tillage treatments. These data suggest that it may be possible to identify genetic components to variation in P nutrition in barley, but that a large interaction with environmental variables may limit the usefulness of any genes or markers discovered for improving P-use efficiency to the conditions under which the screening was performed.